Westonci.ca is the Q&A platform that connects you with experts who provide accurate and detailed answers. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Sure, let's find the polynomial function step-by-step given the roots [tex]\( -2 \)[/tex], [tex]\( 4 \)[/tex], [tex]\( 3 + i \)[/tex], and [tex]\( 3 - i \)[/tex], and the condition [tex]\( f(-3) = 15 \)[/tex].
### Step-by-Step Solution:
1. Identify the roots and their implications:
- The given roots are [tex]\( -2 \)[/tex], [tex]\( 4 \)[/tex], [tex]\( 3 + i \)[/tex], and [tex]\( 3 - i \)[/tex]. Since the polynomial must have real coefficients, the complex roots have to appear in conjugate pairs [tex]\( (3 + i) \)[/tex] and [tex]\( (3 - i) \)[/tex].
2. Form the polynomial from the roots:
- A polynomial can be written as the product of its factors based on its roots. Thus, the polynomial [tex]\( f(x) \)[/tex] with these roots can be written as:
[tex]\[ f(x) = k (x + 2)(x - 4)\left( x - (3+i) \right)\left( x - (3-i) \right) \][/tex]
where [tex]\( k \)[/tex] is a constant multiplier to be determined.
3. Simplify the polynomial:
- First, simplify the factors involving the complex roots:
[tex]\[ (x - (3+i))(x - (3-i)) = \left((x - 3) - i\right)\left((x - 3) + i\right) \][/tex]
Using the difference of squares:
[tex]\[ (x - 3)^2 - i^2 = (x - 3)^2 + 1 = x^2 - 6x + 9 + 1 = x^2 - 6x + 10 \][/tex]
- Now the polynomial becomes:
[tex]\[ f(x) = k (x + 2)(x - 4)(x^2 - 6x + 10) \][/tex]
4. Expand the polynomial:
- Multiply out the factors:
[tex]\[ (x + 2)(x - 4) = x^2 - 4x + 2x - 8 = x^2 - 2x - 8 \][/tex]
[tex]\[ f(x) = k (x^2 - 2x - 8)(x^2 - 6x + 10) \][/tex]
Expanding this product:
[tex]\[ (x^2 - 2x - 8)(x^2 - 6x + 10) \ = x^4 - 6x^3 + 10x^2 - 2x^3 + 12x^2 - 20x - 8x^2 + 48x - 80 \ = x^4 - 8x^3 + 14x^2 + 28x - 80 \][/tex]
5. Include the constant multiplier [tex]\( k \)[/tex]:
- Now we have:
[tex]\[ f(x) = k \left( x^4 - 8x^3 + 14x^2 + 28x - 80 \right) \][/tex]
6. Determine [tex]\( k \)[/tex] using the condition [tex]\( f(-3) = 15 \)[/tex]:
- Substitute [tex]\( x = -3 \)[/tex] and [tex]\( f(-3) = 15 \)[/tex]:
[tex]\[ 15 = k \left( (-3)^4 - 8(-3)^3 + 14(-3)^2 + 28(-3) - 80 \right) \][/tex]
Calculate the value inside the brackets:
[tex]\[ 15 = k \left( 81 + 216 + 126 - 84 - 80 \right) = k \left( 81 + 216 + 126 - 84 - 80 \right) = k (259) \][/tex]
So,
[tex]\[ k = \frac{15}{259} \][/tex]
7. Write the final polynomial:
- Substitute the value of [tex]\( k \)[/tex] back into the polynomial:
[tex]\[ f(x) = \frac{15}{259} \left( x^4 - 8x^3 + 14x^2 + 28x - 80 \right) \][/tex]
Distribute the constant:
[tex]\[ f(x) = \frac{15}{259} x^4 - \frac{120}{259} x^3 + \frac{210}{259} x^2 + \frac{420}{259} x - \frac{1200}{259} \][/tex]
Therefore, the polynomial function of degree 4 with only real coefficients based on the given roots and condition is:
[tex]\[ f(x) = \frac{15}{259} x^4 - \frac{120}{259} x^3 + \frac{210}{259} x^2 + \frac{420}{259} x - \frac{1200}{259} \][/tex]
### Step-by-Step Solution:
1. Identify the roots and their implications:
- The given roots are [tex]\( -2 \)[/tex], [tex]\( 4 \)[/tex], [tex]\( 3 + i \)[/tex], and [tex]\( 3 - i \)[/tex]. Since the polynomial must have real coefficients, the complex roots have to appear in conjugate pairs [tex]\( (3 + i) \)[/tex] and [tex]\( (3 - i) \)[/tex].
2. Form the polynomial from the roots:
- A polynomial can be written as the product of its factors based on its roots. Thus, the polynomial [tex]\( f(x) \)[/tex] with these roots can be written as:
[tex]\[ f(x) = k (x + 2)(x - 4)\left( x - (3+i) \right)\left( x - (3-i) \right) \][/tex]
where [tex]\( k \)[/tex] is a constant multiplier to be determined.
3. Simplify the polynomial:
- First, simplify the factors involving the complex roots:
[tex]\[ (x - (3+i))(x - (3-i)) = \left((x - 3) - i\right)\left((x - 3) + i\right) \][/tex]
Using the difference of squares:
[tex]\[ (x - 3)^2 - i^2 = (x - 3)^2 + 1 = x^2 - 6x + 9 + 1 = x^2 - 6x + 10 \][/tex]
- Now the polynomial becomes:
[tex]\[ f(x) = k (x + 2)(x - 4)(x^2 - 6x + 10) \][/tex]
4. Expand the polynomial:
- Multiply out the factors:
[tex]\[ (x + 2)(x - 4) = x^2 - 4x + 2x - 8 = x^2 - 2x - 8 \][/tex]
[tex]\[ f(x) = k (x^2 - 2x - 8)(x^2 - 6x + 10) \][/tex]
Expanding this product:
[tex]\[ (x^2 - 2x - 8)(x^2 - 6x + 10) \ = x^4 - 6x^3 + 10x^2 - 2x^3 + 12x^2 - 20x - 8x^2 + 48x - 80 \ = x^4 - 8x^3 + 14x^2 + 28x - 80 \][/tex]
5. Include the constant multiplier [tex]\( k \)[/tex]:
- Now we have:
[tex]\[ f(x) = k \left( x^4 - 8x^3 + 14x^2 + 28x - 80 \right) \][/tex]
6. Determine [tex]\( k \)[/tex] using the condition [tex]\( f(-3) = 15 \)[/tex]:
- Substitute [tex]\( x = -3 \)[/tex] and [tex]\( f(-3) = 15 \)[/tex]:
[tex]\[ 15 = k \left( (-3)^4 - 8(-3)^3 + 14(-3)^2 + 28(-3) - 80 \right) \][/tex]
Calculate the value inside the brackets:
[tex]\[ 15 = k \left( 81 + 216 + 126 - 84 - 80 \right) = k \left( 81 + 216 + 126 - 84 - 80 \right) = k (259) \][/tex]
So,
[tex]\[ k = \frac{15}{259} \][/tex]
7. Write the final polynomial:
- Substitute the value of [tex]\( k \)[/tex] back into the polynomial:
[tex]\[ f(x) = \frac{15}{259} \left( x^4 - 8x^3 + 14x^2 + 28x - 80 \right) \][/tex]
Distribute the constant:
[tex]\[ f(x) = \frac{15}{259} x^4 - \frac{120}{259} x^3 + \frac{210}{259} x^2 + \frac{420}{259} x - \frac{1200}{259} \][/tex]
Therefore, the polynomial function of degree 4 with only real coefficients based on the given roots and condition is:
[tex]\[ f(x) = \frac{15}{259} x^4 - \frac{120}{259} x^3 + \frac{210}{259} x^2 + \frac{420}{259} x - \frac{1200}{259} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.